PEMBERDAYAAN MASYARAKAT MELALUI PENDIDIKAN KARAKTER BERBASIS NILAI ISLAM DAN PANCASILADI KECAMATAN MUARA PAWAN KABUPATEN KETAPANG - Syafrudin Syafrudin; Jepi Triono, Ilham, Habib Takul Huda, Fajar Hendrawan, Nurhamdah, Lailatul Fadilah (JOURNAL OF COMMUNITY DEDICATION, 2024)
This Community Service activity aims to empower the community of Muara Pawan District, Ketapang Regency, through character education based on Islamic and Pancasila values. Character education is an urgent need in building a society with integrity, tolerance, and competitiveness, especially amidst the social, cultural, and moral challenges faced by society today. Islamic and Pancasila values are harmoniously combined to form the character of a society that is both religious and nationalistic. The methods used in this activity include counseling, participatory training, simulations, group discussions, and direct assistance in the field. Evaluation is carried out through questionnaires, interviews, and group discussions to measure the effectiveness of the activity. The results of the activity showed that 85% of participants experienced an increase in understanding of Islamic and Pancasila values, 78% were actively involved in the activity, and 75% stated that there were positive changes in social attitudes and behavior. The level of participant satisfaction reached 87%, although facilities and infrastructure still need to be improved. This activity has succeeded in growing collective awareness of the community towards the importance of character education that is based on religious and national values. It is hoped that this program will become a model for sustainable community empowerment and can be replicated in other areas with similar social characteristics.